Writing and the writer - Smith, Frank (Holt, Rinehart, and Winston, 1982)
This second edition includes many new insights from the author's significant experience and from recent research, providing a framework for thinking about the act of writing in both theoretical and practical ways. A completely new chapter on computers and writing is included, as well as more about the role of reading in learning to write, about learning to write at all ages, and about such controversial issues as whether and how genre theory should be taught.